Qualitative and quantitative estimations of phytoconstituents from phoenix sylvestris roots - Shakeeb Akhtar Nehal Ahmad; Rakeshkumar Jat; Rashid Akhtar (International Journal of Pharmacy and Analytical Research, 2022)
Phoenix sylvestris is commonly known as Indian date and is native to India. It is traditionally important and known for its nutritional values throughout the world. It is a rich source of carbohydrate, phenols, amino acids, flavonoids, tannins, alkaloids, terpenoids, dietary fibers, essential vitamins and minerals. Different parts of the plant exhibit diverse medicinal properties such as being antipyretic, cardiotonic, laxative, diuretic and antioxidant. In the present study The root part was selected. Morphological characteristic were performed and transverse section was taken and observed under microscope. Extraction was done by using methanol as solvent in Soxhlet apparatus. Extract was subjected for different phytochemical constituent. Total flavonide and terpenoid were determined and it was observed that Phoenix sylvestris root contains 7.25% total flavonide and 0.25% terpenoide.